2009
DOI: 10.1186/1471-230x-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Visceral obesity and the risk of Barrett's esophagus in Japanese patients with non-alcoholic fatty liver disease

Abstract: BackgroundThe association between obesity and the risk of Barrett's esophagus (BE) is unclear. Furthermore, the association between visceral obesity and the risk of BE is entirely unknown.MethodsWe conducted a retrospective study in 163 patients with non-alcoholic fatty liver disease (NAFLD) who underwent both endoscopy and abdominal CT at an interval of less than a year at our institution. BE was endoscopically diagnosed based on the Prague C & M Criteria. The surface areas of visceral adipose tissue (VAT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…There has been recent interest in the possible role of abdominal obesity in the development of GERD-related disorders [11,16,17,18]. Recent studies have shown abdominal obesity, as defined by the waist circumference (WC) and waist-to-hip ratio (WHR), to be a risk factor for BE independent of the BMI, with the association between BMI and BE being no longer observed after adjustment for the WC and WHR [16,17].…”
Section: Abdominal Obesity Especially Visceral Obesity and The Riskmentioning
confidence: 99%
“…There has been recent interest in the possible role of abdominal obesity in the development of GERD-related disorders [11,16,17,18]. Recent studies have shown abdominal obesity, as defined by the waist circumference (WC) and waist-to-hip ratio (WHR), to be a risk factor for BE independent of the BMI, with the association between BMI and BE being no longer observed after adjustment for the WC and WHR [16,17].…”
Section: Abdominal Obesity Especially Visceral Obesity and The Riskmentioning
confidence: 99%
“…Our previous study suggested that the NAFLD status was positively related to insulin resistance caused by visceral fat accumulation (14), and the inflammatory changes induced by visceral fat accumulation may induce adipocytokine dysregulation (25). Adipocytokine dysregulation, especially reduced secretion of adiponectin, could induce lower sphincter tone, leading to the exacerbation GERD symptoms (10,25). In the present study, there was a weak association between insulin resistance and GERD symptoms measured by the FSSG, which warrants further examination.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies suggested the association between symptoms of GERD and insulin resistance (10,14,25). Our previous study suggested that the NAFLD status was positively related to insulin resistance caused by visceral fat accumulation (14), and the inflammatory changes induced by visceral fat accumulation may induce adipocytokine dysregulation (25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there has been little study of the correlation between obesity and BE in Japan. Akiyama et al [101] reported a retrospective study on the positive association between VAT and BE in Japanese patients with non-alcoholic fatty liver disease, but the strength of the risk of BE was very weak (OR 1.0074, 95 % CI 1.0001-1.0147, p = 0.0472).…”
Section: Obesity and Carcinogenesismentioning
confidence: 99%